A Study on Obesity Among Faculties of a Medical College in Ahmedabad - Sheetal Vyas; Rachna Kapoor; Mitali Solanki; Parsotam Algotar; Suraj Ambre; Jayesh Bagada (Medsci Publications, 2016)
Background: The problem of obesity is on the rise with excessive consumption of processed food and lack of physical exercise. The present study was carried out with objectives to find out the prevalence of obesity and associated factors among the medical professionals. Methods: A Cross-sectional study was carried out amongst 300 faculties of AMC MET medical college and its affiliated LG Hospital. The statistical analysis was done using SPSS version17.0. Results: The study population comprised of 113 (37.67%) females and 187 (62.33%) males. Prevalence of obesity and overweight were 15.7% and 48% respectively. Males were statistically significantly more overweight than females (p value=0.028), but there was no statistically significant difference between obesity among males and females ( p value=0.817). Amongst the male faculties waist circumference was statistically significantly higher in those who consumed junk food frequently. Stress had a positive association with all the parameters in both sexes except waist circumference in males and diastolic BP in females which were not affected by stress. Conclusion: The life style factors like stress, exercises and dietary patterns are closely associated with the obesity and its health impacts. The healthy life style practices should be followed to reduce the burden of non-communicable diseases.